Infectious environmental factors and systemic lupus erythematosus - James, Judith (Henry Stewart Talks, 2007)
Etiology and genetics of SLE, Hormonal influences in SLE, Role of infections in SLE, Infections associated with lupus, Apoptosis in lupus, Infectious bystander effects in SLE, Development of autoantibodies in lupus, Epitope spreading, Molecular mimicry, Epstein-Barr virus and SLE, Lupus specific differences to pathogens, Mounting evidence for the role(s) of infections in SLE
Archived at 2021/02/25